IMPLEMENTASI PENDIDIKAN SENI RUPA DI TAMAN KANAK-KANAK DALAM KEGIATAN MENGGAMBAR BEBAS - Widiyastuti, Endang (Jurnal Inovasi Pendidikan, 2007)
The article discusses the implementation of fine arts education in Kindergarten, specifically in the free drawing study. It is proper if the learning and implementation activities in kindergarten refer to the philosophy and basic purpose determined in law. Teacher is demanded to know the development of their students who are developing accordance to their age (childhood). Teacher conducts learning activity in accordance to the schedule determined by particular strategy (motivation distribution), so the children may remain to express their selves as well as been expected before. In evaluating the children's work, teacher has to refer to the philosophy of free expression approach in that children expression is unique and natural and inside of the substances. There are not any ?true? and ?false? terms in expressing themselves in fine arts. The evaluation system is appreciative, that is accepting and appreciating what the children express or create by showing the possibility of the increase of the quality of the created work of art.